2016
DOI: 10.1007/s11356-016-7363-0
|View full text |Cite
|
Sign up to set email alerts
|

Periphyton: an important regulator in optimizing soil phosphorus bioavailability in paddy fields

Abstract: Periphyton is ubiquitous in paddy field, but its importance in influencing the bioavailability of phosphorus (P) in paddy soil has been rarely recognized. A paddy field was simulated in a greenhouse to investigate how periphyton influences P bioavailability in paddy soil. Results showed that periphyton colonizing on paddy soil greatly reduced P content in paddy floodwater but increased P bioavailability of paddy soil. Specifically, all the contents of water-soluble P (WSP), readily desorbable P (RDP), algal-av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 32 publications
(52 reference statements)
0
33
0
Order By: Relevance
“…A fiber substrate was used for periphytic microorganism enrichment and formation (Wu et al, ). First, the substrate was sterilized, rinsed, and submerged into the medium.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A fiber substrate was used for periphytic microorganism enrichment and formation (Wu et al, ). First, the substrate was sterilized, rinsed, and submerged into the medium.…”
Section: Methodsmentioning
confidence: 99%
“…However, the periphyton in artificial wetlands, such as paddy fields, has rarely been investigated. Our previous work indicated that periphyton significantly affects soil P bioavailability in paddy fields (Wu, Liu, Lu, Wu, & Kerr, ). However, the mechanism by which paddy periphyton affects soil P bioavailability remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…For example, when Ca(II) concentration increased from 0 to 1.2 mM, P i concentration in the suspension decreased by 15% to 48%; and when Fe(II) concentration increased from 0 to 0.2 mM, P i concentration in the suspension decreased by 50%. The Ca(II), Fe(II) and P i concentrations chosen in this study are representative of paddy fields (Kögel-Knabner et al, 2010;Wu et al, 2016). Thus, periphyton propagated in paddy fields during the early stage of rice growth would serve as a sink for P i , thereby decreasing loss to surrounding water bodies.…”
Section: Agronomic and Environmental Implicationsmentioning
confidence: 99%
“…stream, wetlands, and rivers, etc.) [6], periphytic biofilms growing in paddy fields are important due to their potential significance for both agronomy and environmental protection [7]. However, the study of periphytic biofilms is still in its infancy due to periphytic biofilms have been chronically ignored by both agronomists and ecologists.…”
mentioning
confidence: 99%
“…However, the study of periphytic biofilms is still in its infancy due to periphytic biofilms have been chronically ignored by both agronomists and ecologists. Most of the recent studies on periphytic biofilms have focused on the relationship between their microbial composition and their ecological functions [7,8], while the allimportant abiotic composition of the periphytic biofilm, specifically the EPS component, has received only limited attention.…”
mentioning
confidence: 99%